ECONOMIC IDEAS OF CHRISTIANITY AS THE BASIS OF POSSIBLE POST – CRISIS ECONOMIC STRATEGY OF UKRAINE - Литвин, О. Ю. (Scientific Progress & Innovations, 2014)
The principal economics ideas of Christianity are considered in the article. The article analyses some publications by Ukrainian and Russian researchers, church historians and publicists dedicated to study of this problem. In this article the attention is focused on the influence of economics ideas of Christianity on modern economics. We must consider the economic ideas of Christianity, not only in the context of the development of Christianity and economic thinking, but associating them with a possibile national Post - crisis economic strategy of Ukraine.